Economic Uncertainty, Parental Selection, and Children's Educational Outcomes - Arnaud Chevalier; Olivier Marie (Institute for the Study of Labor (IZA), 2015)
After the fall of the Berlin Wall, East Germany experienced an unprecedented temporary drop in fertility driven by economic uncertainty. Using various educational measures, we show that the children born during this nativity slump perform worse from an early age onwards. Consistent with negative selection, mothers who gave birth in that period had worse observed personal characteristics. These children are also less likely to have grown up within stable family environment. Investigating underlying mechanisms reveals that parental educational input and emotional attachment were also lower for these children. Finally, sibling analysis enables us to reject time of birth effects.
Keywords: J13; I20; 330; parental selection; fertility; economic uncertainty; education